Performing MRI Scans on Cochlear Implant and Auditory Brainstem Implant Recipients: Review of 14.5 Years Experience. Issue 5 (June 2020) - Tam, Yu Chuen; Lee, Jennifer W. Y.; Gair, Juliette; Jackson, Cay; Donnelly, Neil P.; Tysome, James R.; Axon, Patrick R.; Bance, Manohar L.
Abstract : Objective: To assess the complication rate of magnetic resonance imaging (MRI) using 1.5 T scanners on cochlear implant (CI) and auditory brainstem implant (ABI) recipients over 14.5 years. Methods: Prospective study conducted in a tertiary referral center for cochlear and auditory brainstem implantation, including patients with neurofibromatosis 2. The primary outcome was complications related to MRI scanning in implant recipients, including failure to complete MRI sessions. The secondary outcome was magnet void size due to MRI scanning with magnet in situ. Results: Ninety-seven patients (21 ABI recipients, 76 CI recipients of whom 23 were bilateral) underwent a total of 428 MRI sessions consisting of 680 MRI procedures, which generated 2, 601 MRI sequences (excluding localizers). Of these, 28/428 (6.5%) MRI sessions were performed with magnet removed, and the remaining 400/428 (93.4%) with the magnet in situ. The overall complication rate per session was 15/428 (3.5%). The majority of complications were accounted for by patient discomfort, in some cases requiring abandoning the scan session, but 5 magnet dislocations were also recorded. There were no cases of implant device failure or excessive demagnetization of the receiver stimulator magnet. For CI and ABI recipients, the implant caused large voids of around 110 mm × 60 mm with the magnet in situ which reduced to 60 mm × 30 mm when the magnet was removed. However, it was usually possible to visualize the internal acoustic meatus and cerebellopontine angle by positioning the implant package higher and further forward compared with conventional positioning. Conclusion: MRI scanning in ABI and CI recipients is generally safe and well tolerated without magnet removal, and carries a low rate of complications. However, patients should be fully informed of the possibility of discomfort, and precautions such as local anesthetic injection and head bandaging may reduce the likelihood of adverse events.